Rapid acceleration of KRAS-mutant pancreatic carcinogenesis via remodeling of tumor immune microenvironment by PPARδ - Liu, Yi; Deguchi, Yasunori; Wei, Daoyan; Liu, Fuyao; Moussalli, Micheline J.; Deguchi, Eriko; Li, Donghui; Wang, Huamin; Valentin, Lovie Ann; Colby, Jennifer K.; Wang, Jing; Zheng, Xiaofeng; et al. (Nature communications, 2022)
Pancreatic intraepithelial neoplasia (PanIN) is a precursor of pancreatic ductal adenocarcinoma (PDAC), which commonly occurs in the general populations with aging. Although most PanIN lesions (PanINs) harbor oncogenic KRAS mutations that initiate pancreatic tumorigenesis; PanINs rarely progress to PDAC. Critical factors that promote this progression, especially targetable ones, remain poorly defined. We show that peroxisome proliferator-activated receptor-delta (PPARδ), a lipid nuclear receptor, is upregulated in PanINs in humans and mice. Furthermore, PPARδ ligand activation by a high-fat diet or GW501516 (a highly selective, synthetic PPARδ ligand) in mutant KRAS G12D ( KRAS mu ) pancreatic epithelial cells strongly accelerates PanIN progression to PDAC. This PPARδ activation induces KRAS mu pancreatic epithelial cells to secrete CCL2, which recruits immunosuppressive macrophages and myeloid-derived suppressor cells into pancreas via the CCL2/CCR2 axis to orchestrate an immunosuppressive tumor microenvironment and subsequently drive PanIN progression to PDAC. Our data identify PPARδ signaling as a potential molecular target to prevent PDAC development in subjects harboring PanINs. Pancreatic intraepithelial neoplasia (PanIN) can develop into pancreatic ductal adenocarcinoma (PDAC), however, the factors which determine how this occurs are unknown. Here, the authors illustrate the role of PPARδ in the upregulation of CCL2, resulting in an immunosuppressive microenvironment, and driving the progression of PanIN to PDAC.